Monogenean ectoparasites in juveniles of Cichla monoculus from the Tarapoto lake, Nanay river, Peru - Arbildo Ortiz, Humberto (2020)
The aim of this study was to identify the monogenean ectoparasites and the parasitic indices of juveniles of Cichla monoculus from the Tarapoto lake, Nanay river, Peru, between July and September 2011. Thirty juveniles were examined (35.9 ± 14.0 g and 14.46 ± 1.97 cm). The fins, nostrils and branchial arches were removed and placed in a petri dish with distilled water for the search of monogeneans. The parasites were fixed in glycerin ammonium-picrate (GAP) to observe the sclerotized structures. There were 2343 monogeneans in the gills and 240 individuals were collected for identification. Three species were identified: Gussevia longihaptor (prevalence = 80%, mean intensity = 5.21 parasite/fish, mean abundance = 4.17 parasite/fish), Gussevia undulata (prevalence = 70%, mean intensity = 4.95 parasite/fish, mean abundance = 3.47 parasite/fish) and Sciadicleithrum ergensi (prevalence = 23.3%, mean intensity = 1.57 parasite/fish, mean abundance = 0.23 parasite/fish). The first two species are considered central species, while the third is considered a satellite species. Likewise, S. ergensi is reported for the first time in Peru and in Cichla monoculus.